Gut content analysis and gonadal stage of slipmouth, Leiognathus equulus (Forsskal, 1775) in Poblacion River, Lawaan, Eastern Samar - Andrade, Emily S.; dela Cruz, Margarita G. (2017)
Diet composition indicates where animals derive their sustenance. In this study, the diet composition and gonadal stage of Leiognathus equulus found in Poblacion River, Lawaan, Eastern Samar were examined. Data collection was done once every month from January to April 2017 in three sampling stations. Results of this study showed the diet composition of Leiognathus equulus to be composed of crustaceans, polychaetes, and smaller fish. Crustacean remains were found in 7.5% of the samples while 5% of the slipmouths had polychaetes in their stomach. Small fishes comprise 37.5% of the food of the fish samples. The rest of the slipmouths examined (50%) had empty stomach which means that their diet may have been composed of plankton as slipmouths are also plankton-feeders. Of the 40 collected samples, only 8 were males. Only 10 individuals out of all the samples were in spawning stage (25%) and all of them had empty stomachs. This study further shows that slipmouths spawn in the brackish portion of the Poblacion River in Lawaan, Eastern Samar.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.